Motivación y la escritura en la modalidad de la enseñanza semipresencial en los niños de cinco años de la Institución Educativa Inicial N° 770 Santa Rosa del Caño, Caballococha 2022 - Pacaya Fasabi, Lissi Margot (2023)
This research has been developed with the purpose of linking motivation and writing in the modality of blended learning in five-year-old children of the initial educational institution No. 770 Santa Rosa del Caño - Caballococha. The research is of a relational type, with a field, cross-sectional and bivariate design. The population considered was 50 children at the initial level, while the sample was 42 for convenience. Observation was used as a technique and an observation guide as an instrument to obtain the data, previously the instruments were validated by expert judgment. The conclusion is that there is no significant relationship between the application of motivation and the writing level of five-year-old children from the Initial Educational Institution No. 770 Santa Rosa del Caño - Caballococha 2022. Because they have a moderate relationship on which is valid with the Rho Spearman correlation coefficient (rs=0.169)